Demanda de nutrientes em cultivares de cenoura - Silva, Jorge Luiz Alves da (Universidade Federal Rural do Semi-Árido, 2019)
Among the production factors, the need for the use of a balanced fertilization, knowing the accumulation of nutrients, increasingly influences the yield. The objective of the present work was to evaluate the nutrient demand of carrot cultivars. The experiments were carried out at Rafael Fernandes Experimental Farm, in the community of Alagoinha, municipality of Mossoró-RN, belonging to the Federal Rural University of Semiarid, from June to September (season 1) and from July to October (season 2) 2017. The characteristics evaluated were: Plant dry mass, macronutrient accumulation and root yield. The experimental design was randomized blocks, using ten treatments and four replications. The treatments consisted of carrot cultivars (Brasilia, BRS Planalto, Kuronam, Supreme, Native, Mariana, Melinda, Amanda, Erica and Francine). The average root yield ranged from 21.25 t ha-1 (BRS Planalto) to 32.31 t ha-1 (Melinda). Carrot cultivars showed differences in nutrient accumulation in both experiments, however, in general, hybrids presented lower nutrient demand. The accumulations obtained in the plant were: potassium> nitrogen> phosphorus> calcium> magnesium. In season 1 the highest accumulation of P (89.94 mg plant-1) was obtained by cultivar Francine, of K and Mg (966.92 and 30.56 mg plant-1) in cultivar Brasilia, while in season 2 the highest accumulation of P, K and Mg (77.35; 1189.92 and 27.24 mg plant-1) was obtained in the cultivar BRS Planalto. For the accumulations of N and Ca there was no significant effect, presenting average values of 270.66 and 72.11 mg plant-1, in that order. The results show that for the leaf mass and root mass variable, there was no significant difference between the cultivars.
Monografia
Keywords: Macronutrientes; Daucus carota L; Épocas de plantio; Nutritional demand; Carrot; Planting times; CIENCIAS AGRARIAS::AGRONOMIA